Natural history of SARS-CoV-2 infection in healthcare workers in Northern Italy - Bongiovanni, M. (J Hosp Infect, 2020)
At present, the time-frame used for the quarantine of individuals with coronavirus disease 2019 (COVID-19) is the entire duration of symptoms plus 14 days after symptom recovery; however, no data have been reported specifically for healthcare workers (HCWs). In the study population of 142 HCWs with COVID-19, the mean time for viral clearance was 31.8 days. Asymptomatic subjects cleared the virus more quickly than symptomatic subjects (22 vs 34.2 days; P<0.0001). The presence of fever at the time of diagnosis was associated with a longer time to viral clearance (relative risk 11.45, 95% confidence interval 8.66–14.25; P<0.0001). These findings may have a significant impact on healthcare strategies for the future management of the COVID-19 pandemic.